THE IMPACT OF ORGANIC FERTILIZER FROM TEMBANG FISH (Sardinella fimbriata) AND COCONUT WATER (Cocos nucifera L) ON THE GROWTH AND FRUIT OF BIRD’S EYE CHILI PLANTS (Capsicum frutescens L.) - Ayu Nikmatul Azizah; Elsje Theodora Maasawet; Herliani Herliani (Jurnal Pendidikan Matematika dan IPA)
Abstract